Effects of Moisture Content and Lime Concentrate on Physiochemical, Mechanical, and Sensory Properties of Quinoa Snacks: An Ancient Andean Crop in Puno, Peru - Carmen Mindani; Edwin O. Baldeón; Vladimiro Ibáñez; Fredy Calizaya; Carmen Taipe; Jorge Zegarra; Melvin Pozo (AgriEngineering)
The growing global demand for healthy, gluten-free snacks has driven the food industry to explore innovative products that fit consumer preferences. This study focused on developing a gluten-free, energy-dense, and crunchy snack called Quispiño, made from quinoa (Chenopodium quinoa Willd.), an ancient crop native to the Andes and particularly significant in Puno, Peru. Natural and desaponified quinoa samples were compared, revealing decreased carbohydrate content (69.75 g to 64.02 g per 100 g) and protein content (13.27 g to 12.90 g per 100 g) after desaponification. Moisture remained around 11.5%, while fiber content significantly decreased in the desaponified quinoa (from 4.39 g to 2.76 g per 100 g). The extrusion process influenced the color of the extrudates, reducing the L* value (from 75.28 to a range of 63.70–69.12), indicating darkening due to the Maillard reaction. Moisture in the extrudates ranged from 3.08% to 6.12%, while firmness varied between 7.25 N and 25.86 N, significantly influencing extrusion temperature. The water solubility index (WSI) ranged from 0.17% to 71.61%, with high values attributed to starch dextrinization during extrusion. The water absorption index (WAI) showed a significant increase, highlighting the physical changes induced by extrusion. The sectional expansion index (SEI) also varied considerably, ranging from 7.33 to 13.08, reflecting the impact of the extrusion process on the final product structure. The optimal sample was identified and subjected to an acceptability test with an untrained panel of 45 evaluators who assessed flavor, color, odor, appearance, and texture. The best-performing treatment was further analyzed for proximate composition, calcium, and iron content to compare with the raw material. The results demonstrate the potential of quinoa as a key ingredient in developing new, expanded, gluten-free snacks that meet the growing demand for nutritious and appealing food products in the global market.